Folia de Reisado de Cabaceiras (Conceição do Coité): (1965-2005) - Brito, Ana Nery Oliveira (2016)
This dissertation analyzes the Festa de Reis (Feast of Kings) in the city of Conceição do Coité, Bahia, between the years 1965 to 2005, focusing on the performance of the Reisado de Cabaceiras Group in a rural community located in this municipality. The proposed research sought to identify the changes and permanence during the festivities, as well as to understand the reasons and instruments used by the “sambadores” (samba dancers) for these changes to occur, how they are being perceived and experienced by the population that participated in the feast, and how the residents of the Cabaceiras community understood and participated in the reinvention process. In addition, it seeks to understand new meanings and appropriations of other forms of religiosity, such as the interreligious dialogue between the religion of African matrices and the Catholic tradition, which makes it plural in relation to other celebrations in praise of the Holy Kings in the interior of Bahia state. We analyze aspects between the sacred and the profane, besides observing conflicts and divergences between the revelers and the municipal authorities. For that, the narratives of these residents and participants, audiovisual records and written sources were primordial methodological resources, in order to understand the peculiarities of this Christmas party. The work intends to contribute to an analysis of the practices of the feast as an expression of popular religiosity, focusing on the dynamics of the Reisado de Cabaceiras Group, its trajectory and its insertion in the urban spaces of the city of Conceição do Coité and Sisaleira Region.